2018
DOI: 10.1111/cuag.12135
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Food System Resilience in Bali, Indonesia: A Moral Economy Approach

Abstract: Food systems in Indonesia and other developing countries have witnessed a rapid change in production, trade, and consumption patterns. The central highlands and northeastern coast of Bali form one such system, with centuries of documented regional trade relations between coastal and highland communities whose food products were complementary. This paper adopts a moral economy approach to explain the decline in local food security at a systemic level, and to explore also how it may be reversed. In particular, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…While moral economy always refers to economic behaviours or arrangements concerned with survival, redistribution, or risk minimisation in early studies (McCarthy 2006 ), it has been expanded to include extra factors such as pleasure, friendship, aesthetics, affection, loyalty, justice and reciprocity (Kloppenburg et al 1996 ). According to Reuter ( 2018 ), the moral economy has become a “culture‐specific moral framework of norms, values, and practices of mutual aid that typically have operated within local societies and their food systems”. It has been applied to the entire food supply processes (production, exchange and consumption) in both first and third world settings (Goodman 2004 ).…”
Section: Theoretical Conceptualization and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While moral economy always refers to economic behaviours or arrangements concerned with survival, redistribution, or risk minimisation in early studies (McCarthy 2006 ), it has been expanded to include extra factors such as pleasure, friendship, aesthetics, affection, loyalty, justice and reciprocity (Kloppenburg et al 1996 ). According to Reuter ( 2018 ), the moral economy has become a “culture‐specific moral framework of norms, values, and practices of mutual aid that typically have operated within local societies and their food systems”. It has been applied to the entire food supply processes (production, exchange and consumption) in both first and third world settings (Goodman 2004 ).…”
Section: Theoretical Conceptualization and Hypothesis Developmentmentioning
confidence: 99%
“…Meanwhile, Reuter ( 2018 ) conducted a case study in Indonesia to evaluate the loss of moral economies caused by the modernization of regional food systems. Through comparing and assessing the developments of a local food system in the central highlands, he found that with the rapid modernization, the investigated area had experienced a significant decrease in biodiversity, food security, and social solidarity.…”
Section: Theoretical Conceptualization and Hypothesis Developmentmentioning
confidence: 99%
“…Allievi et al [293] went even farther and made a strong case for considering "ethics" as the fourth dimension of sustainability. Other scholars referred to moral issues [299,[304][305][306]. In this respect, Reuter [304] argued that greater attention to the moral dimension of food systems will contribute to more successful food security and agricultural development programs.…”
Section: Society and Culturementioning
confidence: 99%
“…Other scholars referred to moral issues [299,[304][305][306]. In this respect, Reuter [304] argued that greater attention to the moral dimension of food systems will contribute to more successful food security and agricultural development programs. Likewise, Bui et al [297] identified inclusive governance and "systemic ethics" (i.e., relating to a systemic understanding of sustainability, including social justice) as key features for initiatives contributing to sustainability transitions in agri-food systems.…”
Section: Society and Culturementioning
confidence: 99%
“…Yet, when exploring the possibilities for multiple potential viable agricultural futures in Ontario (Rotz 2018), it is critical to undertake ethnographic research with farmers whose experiences are not located within the Ontario agricultural core. In offering insight into these experiences, I draw attention to the ways that individual factors shape agricultural persistence, with particular consideration of the social factors and cultural values that can shape the capacity for resilience (Greenhill et al 2009; Herman et al 2018; Reuter 2019).…”
Section: Introductionmentioning
confidence: 99%